Experiences of registered nurse prescribers; a qualitative study. Issue 4 (3rd July 2020) - Pearson, Maria; Papps, Elaine; Walker, Rachael C.
Abstract : Aims : This study aimed to investigate the experiences of registered prescribers and their perceptions of the enablers and barriers to registered prescribing and the value of this fledgling role. Background : The role of prescribing has been extended to registered nurses in New Zealand. By adding the designated prescribing role to a nurse's role, their scope of practice expands and nurses are able to provide patients with holistic care while achieving greater independence and role satisfaction. Yet new nurse prescribers can experience anxiety and fear when confronted with the reality of the responsibility of prescribing. Methods : Sixteen semi-structured interviews were conducted with registered nurse prescribers across New Zealand. Data were analysed using a general inductive approach and thematic analysis utilised to identify themes and sub-themes. Results : Sixteen registered nurse prescribers participated in the study. Three main themes emerged with sub-themes: ability to expand practice, improving access to care, and importance of working in a collaborative team. Participants explained how they enjoyed the challenge and responsibility of the new prescribing role yet were frustrated with the realities of the restrictions of what they could actually prescribe and in some cases lack of role recognition. Registered nurse prescribing also improved access to care as nurses felt they provided more comprehensive care, resulting in reduced wait times, better continuity of care and a reduction in patient costs. The participants highlighted the importance of working in a collaborative team and believed their ability to prescribe maximised clinician time, however cautioned the need for on-going clinical mentorship and a prepared and supportive work environment. Conclusions : The addition of registered nurse prescribing provides a number of advantages to individual nurses in terms of career development and job satisfaction, and to patients and the health care system. The benefits to health care consumers and the health care system align directly to health care priorities of improving equity and access to care. Impact statement : Registered nurse prescribers perceive a number of advantages to the addition of prescribing to their own practice and benefits to patients and the health care system by enabling more accessible and cost-effective care.